The role of bovine colostrum on recovery time and length of hospital stay of acute diarrhea in infants and children: a double-blind randomized controlled trial - IGN Suwarba; Sudaryat S; Hendra S; IKG Suandi; Raka Widiana (Indonesian Pediatric Society, 2006)
Background WHO standard treatment for acute diarrhea remainsunsatisfying to the parents of acute diarrhea patients, particularlythe need of medical treatment. Bovine colostrum contains immuneand growth factors that is thought able to neutralize some agentscausing acute diarrhea in infants and children.Objective To evaluate the efficacy of bovine colostrum as adju-vant therapy on recovery time and length of hospital stay for acutediarrhea in infants and children.Methods A double-blind randomized controlled trial was conductedon infants and children with acute diarrhea admitted to SanglahHospital. Treatment group received standard therapy with bovinecolostrums and control group received standard therapy plus pla-cebo. The primary outcomes were achievement of recovery timeand length of hospital stay. Recovery time was determined by thenumber of days needed to achieve defecation frequency <3 times/day and needed to achieve normal stool consistency.Results Seventy infants and children were enrolled. The treatmentgroup significantly achieved recovery time earlier than the control groupin regard to the time of achieving defecation frequency to <3 times/day [2.31 (0.76) vs 3.34 (1.45); mean difference of -1.03; P= 0.001; CI95% -1.58;-0.48] and normal stool consistency [2.40 (0.77) vs 3.43(1.48); mean difference of -1.03; P = 0.001; CI 95% -1.59;-0.46]. Lengthof hospital stay was shorter in the treatment group than the controlgroup [2.89 (0.78) vs 3.94 (1.53); mean difference of -1.05; P= 0.001;CI 95% (-1.3;-0.7)]. No significant difference was found in mean ofbody weight recovery in two groups [0.47 (0.16) vs 0.49 (0.20); meandifference of -0.03; P=0.556; CI 95%: -0.11;0.06]. Age, nutritionalstatus, breastfeeding, and diarrhea before admission did not influ-ence the study outcome.Conclusion Bovine colostrums as an adjuvant in standard therapyfor acute diarrhea in infants and children is effective in regard toachieve earlier recovery time and shorter length of hospital stay